Effects of tephra falls on vegetation: A Late-Quaternary record from southern Italy - Allen, Judy R. M.; Huntley, Brian (The Journal of ecology, 2018)
1. Impacts of tephra deposition on vegetation are recorded in a series of 10 high temporal resolution absolute pollen diagrams from Lago Grande di Monticchio, each diagram spanning a single tephra deposition event during the last glacial-interglacial cycle. 2. Sediment accumulation rates determined by counting and measurement of annual laminations ("varves") provide an accurate and precise chronology, enabling the minimum recovery time after a tephra fall to be determined. 3. In most cases, pollen accumulation rate was reduced after the tephra fall, indicating reduced vegetation productivity. Tephra deposition events also led to changes in vegetation composition, although these varied in magnitude. 4. The magnitude and duration of the impacts upon the vegetation were related to the thickness of the tephra layer deposited, the thickest layers examined (>250 mm) having minimum recovery times of up to a century and thicker layers generally having greater impacts upon pollen productivity and vegetation composition. 5. Tephra chemistry also influenced the persistence of the impact. 6. The nature of the prevailing vegetation prior to the tephra fall influenced the degree and persistence of the impact. Tephra layers <30 mm thick had minimum recovery times of up to 90 years when they fell on wooded steppe vegetation, whereas cold steppe recovered much more quickly, as did forest. 7. The relative sensitivity of wooded steppe was contrary to our expectations. 8. Of individual pollen taxa, Cupressaceae emerged as particularly sensitive to tephra deposition. 9. Synthesis. Applying absolute pollen analytical methods to a sediment record with a well-supported and precise chronology obtained from a lake in a volcanic region where the vegetation has been subject to numerous tephra deposition events enabled us to explore the impacts of such events. Our results provide evidence of differential impacts upon individual plant taxa and of differential sensitivity of three vegetation types that have prevailed in the region during the last glacial-interglacial cycle. The influences of tephra thickness and chemistry on minimum recovery time were substantial. Our results are relevant to forecasting the potential impacts upon ecosystems of volcanic eruptions.